Fine Tuning Miscibility of Donor/Acceptor through Solid Additives Enables All‐Polymer Solar Cells with 15.6% Efficiency. Issue 10 (24th August 2021) - Li, Zhenye; Peng, Feng; Ying, Lei; Quan, Huilei; Li, Jingwen; Wang, Xingzhu; Wu, Hongbin; Huang, Fei; Cao, Yong
Abstract : Optimization of the photovoltaic performance of all‐polymer solar cells (all‐PSCs) includes delicate control of the film morphology of the light‐harvesting layer. Although miscibility of polymer donors and polymer acceptors plays a critical role in the description of film morphology of all‐PSCs, the mixing thermodynamics is unrevealed. Herein, we demonstrate that by incorporating 1% weight ratio of PC71 BM as the solid additive into the blends of electron‐donating polymer PTzBI‐oF and electron‐accepting polymer PFA1, the miscibility of donor/acceptor can be improved by virtue of forming a favorable phase separation, which leads to an increased charge carrier transport and simultaneously enhanced fill factor. The maximum power conversion efficiency is thereby improved from 14.6% to 15.6%. The miscibility of two components in the photoactive layer can be quantitatively described using the Flory−Huggins interaction parameter ( χ ). In particular, a correlation between the Flory−Huggins parameters of the two components, in terms of phase separation morphology and device performance of all‐PSCs, is established and the mechanism by which PC71 BM is added to this system is explored. This study establishes guidelines for the selection of solid additives when optimizing the efficiency of all‐PSCs and promotes the integration and development of polymer physics and organic photovoltaics. Abstract : The Flory−Huggins parameters of two components, phase separation morphology and device performance of all‐polymer solar cells (all‐PSCs), are investigated for the first time. PC71 BM is used as a solid additive to boost the fill factor (FF) of all‐PSCs based on PTzBI‐oF:PFA1, as the strong interaction between PC71 BM and PTzBI‐oF can decrease the phase separation of PTzBI‐oF:PFA1 blend film.